Analisis Pengaruh TATO, EPS, dan DPR terhadap Harga Saham pada Perusahaan Indeks Sri Kehati Tahun 2020–2024 - Indri Iswardhani, (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study analyzes the effect of Total Asset Turnover (TATO), Earnings per Share (EPS), and Dividend Payout Ratio (DPR) on the stock prices of firms listed in the SRI-KEHATI Index during 2020–2024, employing a quantitative approach and multiple linear regression. The sample was selected purposively based on the following criteria: firms consistently included in the SRI-KEHATI Index throughout 2020–2024, availability of complete annual financial statements, and availability of dividend and stock price data for the observation period. The results indicate that TATO, EPS, and DPR jointly have a significant effect on stock prices, with R²=0.666, meaning 66.6% of the variation in stock prices is explained by the model, while 33.4% is influenced by other factors outside the model. Partially, EPS and DPR have positive and significant effects on stock prices, whereas TATO is not significant at the 5% level. The findings imply that investors in SRI-KEHATI constituents should prioritize per-share profitability (EPS) and dividend policy (DPR) in fundamental assessments, while TATO should be evaluated with regard to sectoral characteristics and each firm’s operational context.